A new step in the development of Zn/LiFePO4 aqueous battery. (2017) - Molkenova, A.; Belgibayeva, A.; Ibrayeva, D.; Sultanov, M.; Zhumagali, S.; Akhmetova, N.; Hara, T.; Bakenov, Z.
Abstract: In recent years, aqueous batteries have gained much attention due to their low production cost and exceptional safety compared to commercial Li-ion battery systems. Three-dimensional (3D) structure could be promising to enhance these batteries energy capacity. In this work, the electrochemical performance of 3D Zn electrode, developed for aqueous rechargeable Zn/LiFePO4 (Zn/LFP) battery system, was studied. Formation of uniformly coated Zn metal on the three-dimensionally organized carbon fibers was verified by field emission scanning electron microscopy (FE-SEM). The electrochemical performance of the battery with this anode was tested for over 50 cycles, where the initial capacity decayed by 11%. Further, poly(methyl methacrylate) (PMMA) and poly(p-phenylene oxide) (PPO) polymer coatings were extensively investigated as a potential separator for the 3D aqueous battery system. Cyclability of PMMA-coated Zn anode was better than that of "plane" Zn; however, the initial capacity of 3D Zn anode was lower than that for the counterpart system.